Upaya Guru Tahfidz dalam Meningkatkan Kemampuan Hafalan Al-Qur’an Peserta Didik yang Lemah Hafalannya di Rumah Tahfidz Ainurrahmah 9 Pasaman Barat - Triyola, Sismi; Wiza, Rahmi (Asian Journal of Islamic Studies and Da'wah, 2023)
It can be seen that in Tahfidz's house, students who are weak in memorizing make the memorization only stop there, and lack concentration in memorizing which makes the students' memorization not increase. This research aims to see the Tahfidz teacher's efforts in improving the ability to memorize the Al-Qur'an for students who are weak at memorizing it at Rumah Tahfidz Ainurrahmah 9 West Pasaman. This research uses a qualitative method with a descriptive approach. Sources were taken from the head of the Tahfidz house, Tahfidz teachers, and students who were weak at memorizing. To obtain data, researchers used observation, interview and documentation guidelines as research instruments. The analysis technique used is the Milles and Huberman analysis technique using data reduction analysis, data presentation and conclusions. The results of the research show that there are several efforts made by Tahfidz teachers to improve the ability to memorize the Al-Qur'an for students whose memorization is weak at Rumah Tahfidz Ainurrahmah 9 West Pasaman in the form of providing muraja'ah assignments, providing motivation and advice, providing additional hours, and providing punishment.